A preparation process of unfired glaze with antibacterial function

By using the chemical bonds of polystyrene microspheres, inorganic fillers and antibacterial dopants and van der Waals forces in firing-free ceramic glaze, a composite crosslinking network structure is formed, and the problems of insufficient densification of glaze and poor adhesion performance are solved, and the preparation of high-performance antibacterial ceramics is realized.

CN118930048BActive Publication Date: 2025-03-21FOSHAN TAOYING NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411005254.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-03-21
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The existing fire-free ceramic glaze is not dense enough during the curing process, resulting in its physical and mechanical properties such as strength and hardness lower than those of sintered ceramics, and the penetration and adhesion properties of antibacterial agents are poor, so the antibacterial effect is not long-lasting enough.

Method used

By adding van der Waals force between polystyrene microspheres and inorganic fillers, the hydrophilicity of polyvinylpyrrolidone, and the chemical bonds and van der Waals force in the antibacterial dopants to the glaze, a composite crosslinking network structure is formed, which enhances the binding force between the antibacterial dopants and the glaze and improves the antibacterial effect.

Benefits of technology

It improves the comprehensive performance of glaze, enhances the antibacterial effect, ensures the stability and durability of antibacterial properties, and meets the high-performance needs of antibacterial ceramics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004962839990000121
    Figure BDA0004962839990000121
  • Figure BDA0004962839990000131
    Figure BDA0004962839990000131
Patent Text Reader

Abstract

The present invention relates to a process for preparing an unfired glaze with antibacterial function, and belongs to the technical field of ceramic processing. The present invention discloses a process for preparing an unfired glaze with antibacterial function, wherein glaze C is prepared by glaze A and glaze B, and glaze C, an antibacterial dopant, melamine formaldehyde resin, etc. are mixed to obtain an unfired glaze with antibacterial function. The comprehensive performance of the glaze is improved by the van der Waals force between polystyrene microspheres and inorganic fillers, the hydrophilicity of polyvinyl pyrrolidone, and the chemical bonds and van der Waals forces in the antibacterial dopant; in addition, by adding a silane coupling agent, a silicate curing agent, a photocuring initiator and melamine formaldehyde resin, a composite cross-linked network structure is formed, the binding force between the antibacterial dopant and the glaze is enhanced, and the antibacterial effect is synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic processing and relates to a process for preparing a firing-free glaze with antibacterial function. Background Art

[0002] Ceramics are widely used in many fields due to their heat resistance and corrosion resistance. However, the traditional ceramic preparation process usually involves a high-temperature sintering process, which not only consumes a lot of energy, but also emits a lot of carbon dioxide and other greenhouse gases. The sintering process may also produce other harmful gases and solid waste, causing pollution to air quality and the working environment. In view of this, companies are actively researching unfired ceramic glaze technology, which solidifies ceramic glazes through low-temperature treatment or chemical curing methods, which can significantly reduce energy consumption and environmental pollution.

[0003] On the other hand, with the development of society and people's increasing attention to health and quality of life, the demand for antibacterial ceramic glazes is also growing. Although the antibacterial ceramic glazes prepared by the existing unfired technology have made progress in reducing energy consumption and environmental pollution, there are still some technical challenges. Due to the insufficient densification and high porosity of unfired ceramics during the curing process, their physical and mechanical properties such as strength and hardness may be lower than those of sintered ceramics, and they are prone to breakage when subjected to pressure or impact, which limits their application in some fields. In addition, the penetration and adhesion properties of antibacterial agents in unfired ceramics are poor, the compatibility is poor, and they are easy to fall off or be washed away, resulting in weakened antibacterial ability and insufficiently lasting antibacterial effect, which cannot meet the expected antibacterial needs. Summary of the invention

[0004] The purpose of the present invention is to provide a process for preparing an unfired glaze with antibacterial function, which improves the comprehensive performance of the glaze through the van der Waals force between polystyrene microspheres and inorganic fillers, the hydrophilicity of polyvinyl pyrrolidone, and the chemical bonds and van der Waals forces in the antibacterial dopant; in addition, by adding a silane coupling agent, a silicate curing agent, a photocuring initiator and a melamine formaldehyde resin, a composite cross-linked network structure is formed, the binding force between the antibacterial dopant and the glaze is enhanced, and the antibacterial effect is synergistically improved.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A process for preparing an unfired glaze with antibacterial function, characterized in that the process for preparing an unfired glaze with antibacterial function comprises the following steps:

[0007] (1) After mixing kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres and deionized water, polyvinyl pyrrolidone is added, sodium hydroxide solution is added dropwise to adjust the pH, stirred for 4 to 12 minutes, allowed to stand for 18 to 36 hours, the ball milling speed is set to 50 to 250 rpm, ball milled for 20 to 30 minutes, and then passed through a 100 to 200 mesh sieve to obtain glaze A;

[0008] (2) ball milling lithium aluminum silicate powder, cordierite powder and glass fiber at a ball milling speed of 100 to 200 rpm for 10 to 20 minutes, and passing through a 200 to 300 mesh sieve to obtain a mixed powder; adding the mixed powder to an ethanol solution, stirring for 5 to 15 minutes, and then adding a silane coupling agent, a silicate curing agent, a photocuring initiator and a polyvinyl alcohol solution in sequence while stirring, adding a sodium hydroxide solution dropwise to adjust the pH, and ultrasonically dispersing the mixture at 40 to 60 kHz and 150 to 250 W for 30 to 50 minutes to obtain a glaze B;

[0009] (3) mixing glaze A and glaze B to obtain glaze C;

[0010] (4) mixing nano zinc oxide, yttrium oxide, chitosan solution and isooctyl acrylate at 60 to 80° C. for 30 to 50 minutes, adding hexadecyltrimethylammonium bromide and polymethyl methacrylate, and mixing at 70 to 90° C. for 40 to 50 minutes to obtain an antibacterial dopant;

[0011] (5) The antibacterial dopant is added to glaze C, and after ultrasonic dispersion for 20 to 40 min at 40 to 60 kHz and 150 to 250 W, polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water are added, mixed at 50 to 70 ° C for 1 to 2 h, and cured at room temperature for 12 to 36 h to obtain an unfired glaze with antibacterial function.

[0012] Furthermore, the mass ratio of kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres, polyvinyl pyrrolidone and deionized water in step (1) is 10-12: 8.7-9.5: 4.6-6.2: 3.7-5.1: 4.4-6: 4.1-5.5: 3.5-4.9: 1.1-2.7: 20-26.

[0013] Furthermore, the mass ratio of lithium aluminum silicate powder, cordierite powder, glass fiber, ethanol solution, silane coupling agent, silicate curing agent, photocuring initiator and polyvinyl alcohol solution in step (2) is 8-10: 5-7: 1.8-3.6: 16-24: 0.8-2.6: 0.86-1.5: 1.49-2.63: 6-12.

[0014] Furthermore, the concentration of the ethanol solution is 60-80%; the silicate curing agent is sodium silicate adhesive; the photocuring initiator is dibutyltin dilaurate; and the polyvinyl alcohol solution is a mixture of polyvinyl alcohol and deionized water in a mass ratio of 0.25-0.43:1.

[0015] Furthermore, the glaze C in the step (3) is composed of the glaze A and the glaze B in a mass ratio of 0.71-0.83:0.36-0.48.

[0016] Furthermore, the mass ratio of nano zinc oxide, yttrium oxide, chitosan solution, isooctyl acrylate, hexadecyltrimethylammonium bromide and polymethyl methacrylate in step (4) is 8.5-10.1:3.6-5.2:2.2-4.6:1.5-2.7:2.1-3.5:0.9-1.8.

[0017] Furthermore, the particle size of the nano zinc oxide is 50-90 nm; the concentration of the deacetylated chitosan solution is 0.2-0.5 mol / L.

[0018] Furthermore, in the step (5), the mass ratio of glaze C, antibacterial dopant, polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water is 8-12: 2.2-3: 1.2-2: 1.7-3.1: 5-10: 20-30.

[0019] Furthermore, the polyvinyl alcohol solution is prepared by mixing polyvinyl alcohol and deionized water in a mass ratio of 0.45 to 0.51:1.

[0020] Furthermore, the concentration of the sodium hydroxide solution is 0.4-0.6 mol / L; the pH is adjusted to 7.8-8.6; and the silane coupling agent is at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

[0021] Beneficial effects of the present invention:

[0022] (1) The polystyrene microspheres in the glaze A of the present invention can provide additional pore space for the glaze. The van der Waals force between the polystyrene microspheres and inorganic fillers such as kaolin and diatomaceous earth helps to disperse the microspheres in the inorganic filler and reduce agglomeration. The hydrophilicity of polyvinyl pyrrolidone forms a protective layer to further prevent agglomeration, thereby maintaining the uniformity and stable pore structure of the glaze and improving the comprehensive performance of the glaze.

[0023] (2) The ionic bonds formed between the metal ions and oxygen ions in the nano zinc oxide and yttrium oxide in the antibacterial dopant of the present invention are conducive to the formation of antibacterial mixed particles. The polysaccharide molecules in deacetylated chitosan contain a large number of hydroxyl groups, which form hydrogen bonds with the metal ions on the surface of the antibacterial mixed particles. In addition, van der Waals forces exist between the polysaccharide chains and between the polysaccharide chains and the antibacterial mixed particles, which are conducive to improving the dispersibility and stability of the antibacterial mixed particles and synergistically providing a broad-spectrum antibacterial effect. Furthermore, there is a hydrophobic effect between the alkyl chains of isooctyl acrylate and the alkyl chains of hexadecyltrimethylammonium bromide and the surface of the antibacterial mixed particles, which is conducive to the mixing and dispersion of organic and inorganic components and improves the dispersibility and stability of the antibacterial agent in the glaze. Furthermore, the components cooperate with polymethyl methacrylate to form a polymer network, which effectively fixes the antibacterial components and improves the antibacterial effect.

[0024] (3) The lithium aluminum silicate powder, cordierite powder, and glass fiber composite material in the glaze B of the present invention have a low thermal expansion coefficient. Finer particles are obtained by ball milling and embedded in the pores of the glaze A, thereby improving the mechanical properties of the glaze, helping the material to maintain dimensional stability when the temperature changes, reducing cracks and defects caused by thermal stress, and facilitating non-firing molding. Furthermore, three auxiliary agents, namely, a silane coupling agent, a silicate curing agent, and a photocuring initiator, are added and mechanically mixed to improve the dispersibility of the three auxiliary agents in the glaze and promote interaction with the melamine formaldehyde resin. The molecular structure of the silane coupling agent contains active groups, which react chemically with the metal oxide on the surface of the inorganic filler to form The chemical bonds can improve the interfacial compatibility between the filler and the melamine formaldehyde resin and enhance the binding force. When the silicate curing agent is dissolved in water, the oxygen bridge bonds between the silicate molecules form a three-dimensional network structure. The photocuring initiator can induce the double bonds in the melamine formaldehyde resin to cross-link and form a composite cross-linked network structure together. The chemical bonds and physical adsorption in the composite cross-linked network structure can enhance the binding force between the antibacterial dopant and the glaze to prevent it from falling off or migrating during use, thereby maintaining the stability and durability of the antibacterial performance. In addition, the pores in the composite cross-linked network structure can serve as a channel for the antibacterial dopant to penetrate, allowing it to penetrate deeper into the interior of the glaze, thereby enhancing the antibacterial effect.

[0025] (4) The unfired glaze with antibacterial function of the present invention improves the comprehensive performance of the glaze through the van der Waals force between polystyrene microspheres and inorganic fillers, the hydrophilicity of polyvinyl pyrrolidone, and the chemical bonds and van der Waals forces in the antibacterial dopant; in addition, by adding silane coupling agent, silicate curing agent, photocuring initiator and melamine formaldehyde resin, a composite cross-linked network structure is formed, which enhances the binding force between the antibacterial dopant and the glaze, thereby synergistically improving the antibacterial effect. DETAILED DESCRIPTION

[0026] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0027] Example 1

[0028] A process for preparing an unfired glaze with antibacterial function comprises the following steps:

[0029] (1) After mixing kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres and deionized water, polyvinyl pyrrolidone was added, sodium hydroxide solution was added dropwise to adjust the pH, stirred for 4 minutes, allowed to stand for 18 hours, the ball milling speed was set to 50 rpm, ball milled for 20 minutes, and passed through a 100 mesh sieve to obtain glaze A;

[0030] (2) ball milling lithium aluminum silicate powder, cordierite powder and glass fiber at a ball mill speed of 100 rpm for 10 min, and passing through a 200-mesh sieve to obtain a mixed powder; adding the mixed powder to an ethanol solution, stirring for 5 min, and then adding a silane coupling agent, a silicate curing agent, a photocuring initiator and a polyvinyl alcohol solution in sequence while stirring, dropping a sodium hydroxide solution to adjust the pH, and ultrasonically dispersing at 40 kHz and 150 W for 30 min to obtain glaze B;

[0031] (3) mixing glaze A and glaze B to obtain glaze C;

[0032] (4) mixing nano zinc oxide, yttrium oxide, chitosan solution and isooctyl acrylate at 60° C. for 30 minutes, then adding hexadecyltrimethylammonium bromide and polymethyl methacrylate, and mixing at 70° C. for 40 minutes to obtain an antibacterial dopant;

[0033] (5) The antibacterial dopant was added to glaze C, and after ultrasonic dispersion at 40 kHz and 150 W for 20 min, polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water were added, mixed at 50 ° C for 1 h, and cured at room temperature for 12 h to obtain an unfired glaze with antibacterial function.

[0034] The mass ratio of kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres, polyvinyl pyrrolidone and deionized water in step (1) of this embodiment is 10:8.7:4.6:3.7:4.4:4.1:3.5:1.1:20.

[0035] The mass ratio of lithium aluminum silicate powder, cordierite powder, glass fiber, ethanol solution, silane coupling agent, silicate curing agent, photocuring initiator and polyvinyl alcohol solution in step (2) of this embodiment is 8:5:1.8:16:0.8:0.86:1.49:6.

[0036] The concentration of the ethanol solution in this embodiment is 60%; the silicate curing agent in this embodiment is sodium silicate adhesive; the photocuring initiator in this embodiment is dibutyltin dilaurate; the polyvinyl alcohol solution in this embodiment is a mixture of polyvinyl alcohol and deionized water in a mass ratio of 0.25:1.

[0037] The glaze C in step (3) of this embodiment is composed of the glaze A of this embodiment and the glaze B of this embodiment in a mass ratio of 0.71:0.36.

[0038] The mass ratio of nano zinc oxide, yttrium oxide, chitosan solution, isooctyl acrylate, hexadecyltrimethylammonium bromide and polymethyl methacrylate in step (4) of this embodiment is 8.5:3.6:2.2:1.5:2.1:0.9.

[0039] The particle size of the nano zinc oxide in this embodiment is 50 nm; the concentration of the chitosan solution in this embodiment is 0.2 mol / L.

[0040] The mass ratio of glaze C, antibacterial dopant, polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water in step (5) of this embodiment is 8:2.2:1.2:1.7:5:20.

[0041] The polyvinyl alcohol solution of this embodiment is prepared by mixing polyvinyl alcohol and deionized water in a mass ratio of 0.45:1.

[0042] The concentration of the sodium hydroxide solution in this embodiment is 0.4 mol / L; the pH of this embodiment is adjusted to 7.8; and the silane coupling agent in this embodiment is γ-aminopropyltrimethoxysilane.

[0043] Example 2

[0044] A process for preparing an unfired glaze with antibacterial function comprises the following steps:

[0045] (1) After mixing kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres and deionized water, polyvinyl pyrrolidone was added, sodium hydroxide solution was added dropwise to adjust the pH, stirred for 12 minutes, allowed to stand for 36 hours, the ball milling speed was set to 250 rpm, ball milled for 30 minutes, and passed through a 200 mesh sieve to obtain glaze A;

[0046] (2) milling lithium aluminum silicate powder, cordierite powder and glass fiber at a ball mill speed of 200 rpm for 20 min, and passing through a 300-mesh sieve to obtain a mixed powder; adding the mixed powder to an ethanol solution, stirring for 15 min, and then adding a silane coupling agent, a silicate curing agent, a photocuring initiator and a polyvinyl alcohol solution in sequence while stirring, adding a sodium hydroxide solution dropwise to adjust the pH, and ultrasonically dispersing the mixture at 60 kHz and 250 W for 50 min to obtain glaze B;

[0047] (3) mixing glaze A and glaze B to obtain glaze C;

[0048] (4) mixing nano zinc oxide, yttrium oxide, chitosan solution and isooctyl acrylate at 80° C. for 50 min, then adding hexadecyltrimethylammonium bromide and polymethyl methacrylate, and mixing at 90° C. for 50 min to obtain an antibacterial dopant;

[0049] (5) The antibacterial dopant was added to glaze C, and after ultrasonic dispersion at 60 kHz and 250 W for 40 min, polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water were added, mixed at 70 ° C for 2 h, and cured at room temperature for 36 h to obtain an unfired glaze with antibacterial function.

[0050] The mass ratio of kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres, polyvinyl pyrrolidone and deionized water in step (1) of this embodiment is 12:9.5:6.2:5.1:6:5.5:4.9:2.7:26.

[0051] The mass ratio of lithium aluminum silicate powder, cordierite powder, glass fiber, ethanol solution, silane coupling agent, silicate curing agent, photocuring initiator and polyvinyl alcohol solution in step (2) of this embodiment is 10:7:3.6:24:2.6:1.5:2.63:12.

[0052] The concentration of the ethanol solution in this embodiment is 80%; the silicate curing agent in this embodiment is sodium silicate adhesive; the photocuring initiator in this embodiment is dibutyltin dilaurate; the polyvinyl alcohol solution in this embodiment is a mixture of polyvinyl alcohol and deionized water in a mass ratio of 0.43:1.

[0053] The glaze C in step (3) of this embodiment is composed of the glaze A of this embodiment and the glaze B of this embodiment in a mass ratio of 0.83:0.48.

[0054] The mass ratio of nano zinc oxide, yttrium oxide, chitosan solution, isooctyl acrylate, hexadecyltrimethylammonium bromide and polymethyl methacrylate in step (4) of this embodiment is 10.1:5.2:4.6:2.7:3.5:1.8.

[0055] The particle size of the nano zinc oxide in this embodiment is 90 nm; the concentration of the chitosan solution in this embodiment is 0.5 mol / L.

[0056] The mass ratio of glaze C, antibacterial dopant, polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water in step (5) of this embodiment is 12:3:2:3.1:10:30.

[0057] The polyvinyl alcohol solution of this embodiment is prepared by mixing polyvinyl alcohol and deionized water in a mass ratio of 0.51:1.

[0058] The concentration of the sodium hydroxide solution in this embodiment is 0.6 mol / L; the pH of this embodiment is adjusted to 8.6; and the silane coupling agent in this embodiment is γ-aminopropyltrimethoxysilane.

[0059] Example 3

[0060] A process for preparing an unfired glaze with antibacterial function comprises the following steps:

[0061] (1) After mixing kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres and deionized water, polyvinyl pyrrolidone was added, sodium hydroxide solution was added dropwise to adjust the pH, stirred for 8 minutes, allowed to stand for 27 hours, the ball milling speed was set to 150 rpm, ball milled for 25 minutes, and passed through a 150 mesh sieve to obtain glaze A;

[0062] (2) milling lithium aluminum silicate powder, cordierite powder and glass fiber at a ball milling speed of 150 rpm for 15 min, and passing through a 250-mesh sieve to obtain a mixed powder; adding the mixed powder to an ethanol solution, stirring for 10 min, and then sequentially adding a silane coupling agent, a silicate curing agent, a photocuring initiator and a polyvinyl alcohol solution while stirring, dropping a sodium hydroxide solution to adjust the pH, and ultrasonically dispersing the mixture at 50 kHz and 200 W for 40 min to obtain a glaze B;

[0063] (3) mixing glaze A and glaze B to obtain glaze C;

[0064] (4) mixing nano zinc oxide, yttrium oxide, chitosan solution and isooctyl acrylate at 70° C. for 40 minutes, then adding hexadecyltrimethylammonium bromide and polymethyl methacrylate, and mixing at 80° C. for 45 minutes to obtain an antibacterial dopant;

[0065] (5) The antibacterial dopant was added to glaze C, and after ultrasonic dispersion at 50 kHz and 200 W for 30 min, polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water were added, mixed at 60 ° C for 1.5 h, and cured at room temperature for 24 h to obtain an unfired glaze with antibacterial function.

[0066] The mass ratio of kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres, polyvinyl pyrrolidone and deionized water in step (1) of this embodiment is 11:9.1:5.2:4.4:5.2:4.8:4.2:1.9:23.

[0067] The mass ratio of lithium aluminum silicate powder, cordierite powder, glass fiber, ethanol solution, silane coupling agent, silicate curing agent, photocuring initiator and polyvinyl alcohol solution in step (2) of this embodiment is 9:6:2.7:20:1.7:1.18:2.06:9.

[0068] The concentration of the ethanol solution in this embodiment is 70%; the silicate curing agent in this embodiment is sodium silicate adhesive; the photocuring initiator in this embodiment is dibutyltin dilaurate; the polyvinyl alcohol solution in this embodiment is a mixture of polyvinyl alcohol and deionized water in a mass ratio of 0.34:1.

[0069] The glaze C in step (3) of this embodiment is composed of the glaze A of this embodiment and the glaze B of this embodiment in a mass ratio of 0.77:0.42.

[0070] The mass ratio of nano zinc oxide, yttrium oxide, chitosan solution, isooctyl acrylate, hexadecyltrimethylammonium bromide and polymethyl methacrylate in step (4) of this embodiment is 9.3:4.4:3.4:2.1:2.8:1.3.

[0071] The particle size of the nano zinc oxide in this embodiment is 70 nm; the concentration of the chitosan solution in this embodiment is 0.35 mol / L.

[0072] The mass ratio of glaze C, antibacterial dopant, polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water in step (5) of this embodiment is 10:2.6:1.6:2.4:7.5:25.

[0073] The polyvinyl alcohol solution of this embodiment is prepared by mixing polyvinyl alcohol and deionized water in a mass ratio of 0.48:1.

[0074] The concentration of the sodium hydroxide solution in this embodiment is 0.5 mol / L; the pH of this embodiment is adjusted to 8.2; and the silane coupling agent in this embodiment is γ-aminopropyltrimethoxysilane.

[0075] Comparative Example 1

[0076] On the basis of Example 3, the polystyrene microspheres in glaze A were removed and replaced with kaolin of equal weight, and other conditions were consistent with Example 3.

[0077] Comparative Example 2

[0078] On the basis of Example 3, the polyvinyl pyrrolidone in glaze A was removed and replaced with an equal weight of deionized water. Other conditions were the same as those in Example 3.

[0079] Comparative Example 3

[0080] On the basis of Example 3, the lithium aluminum silicate powder in glaze B was removed and replaced with an equal weight of cordierite powder. Other conditions were the same as those in Example 3.

[0081] Comparative Example 4

[0082] On the basis of Example 3, the cordierite powder in glaze B was removed and replaced with glass fiber of equal weight, and other conditions were consistent with Example 3.

[0083] Comparative Example 5

[0084] On the basis of Example 3, the glass fiber in glaze B was removed and replaced with an equal weight of lithium aluminum silicate powder. Other conditions were the same as those in Example 3.

[0085] Comparative Example 6

[0086] On the basis of Example 3, the silane coupling agent in glaze B was removed and replaced with an equal weight of polyvinyl alcohol solution. Other conditions were the same as those in Example 3.

[0087] Comparative Example 7

[0088] On the basis of Example 3, the silicate curing agent in the glaze B was removed and replaced with an equal weight of a photocuring initiator. Other conditions were the same as those in Example 3.

[0089] Comparative Example 8

[0090] On the basis of Example 3, the photocuring initiator in glaze B was removed and replaced with an equal weight of silicate curing agent. Other conditions were the same as those in Example 3.

[0091] Comparative Example 9

[0092] On the basis of Example 3, yttrium oxide in the antibacterial dopant was removed and replaced with an equal weight of nano zinc oxide, and other conditions were consistent with Example 3.

[0093] Comparative Example 10

[0094] On the basis of Example 3, the chitosan solution in the antibacterial dopant was removed and replaced with an equal weight of deionized water. Other conditions were the same as those in Example 3.

[0095] Comparative Example 11

[0096] On the basis of Example 3, isooctyl acrylate in the antibacterial dopant was removed and replaced with an equal weight of hexadecyltrimethylammonium bromide, and other conditions were consistent with Example 3.

[0097] Comparative Example 12

[0098] On the basis of Example 3, the hexadecyltrimethylammonium bromide in the antibacterial dopant was removed and replaced with an equal weight of isooctyl acrylate. Other conditions were the same as those in Example 3.

[0099] Comparative Example 13

[0100] On the basis of Example 3, the polymethyl methacrylate in the antibacterial dopant was removed and replaced with an equal weight of deionized water. Other conditions were consistent with those in Example 3.

[0101] Comparative Example 14

[0102] On the basis of Example 3, the melamine formaldehyde resin in step (5) was removed and replaced with an equal weight of deionized water. Other conditions were the same as those in Example 3.

[0103] The unfired glaze with antibacterial function prepared by Examples 1 to 3 and Comparative Examples 1 to 14 was evenly coated on the fired blank, with a coating amount of 500 g / m 2 , and cured at 60°C for 30 minutes to obtain unfired tiles with antibacterial function.

[0104] The flat pull bonding strength of the glaze was tested according to JG / T55-2018; the Mohs hardness of the glaze was tested by the Mohs hardness pen scratching method; the antibacterial performance requirement was ≥90% according to the test method in Appendix A of the standard "JC / T 897-2014 (2017) Antibacterial Properties of Antibacterial Ceramic Products". The test results are shown in Table 1 below.

[0105] Table 1 Performance test of unfired tiles

[0106]

[0107]

[0108] As shown in Table 1, the flat pull bonding strength of the unfired ceramic tile prepared by the glaze prepared by Examples 1 to 3 is ≥1.73MPa, the Mohs hardness is 6, and the antibacterial performance is ≥97%. The test results are significantly better than the unfired ceramic tile prepared by Comparative Examples 1 to 14. The main reason is that Comparative Examples 1 to 14 replace certain components in the preparation method of the present invention, which affects the molecular interaction and mechanical properties between the overall components. For example, Comparative Example 14 removes the melamine formaldehyde resin in the preparation method, and cannot form a composite cross-linked network structure, thereby affecting the compatibility of the binding agent between the antibacterial component and the glaze, and the flat pull bonding strength and Mohs hardness of the glaze are reduced, affecting the overall antibacterial performance. While Comparative Examples 1 to 8 all replaced the glaze components, and Comparative Examples 9 to 13 changed the antibacterial dopant, and could not form the interweaving, penetration, and synergistic system of the inorganic filler and the organic filler in the present invention, thereby affecting the performance of the unfired ceramic tile in the glaze flat pull bonding strength, Mohs hardness and antibacterial performance.

[0109] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A process for preparing an unfired glaze with antibacterial function, characterized in that: The process for preparing the unfired glaze with antibacterial function comprises the following steps: (1) After mixing kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres and deionized water, polyvinyl pyrrolidone was added, and sodium hydroxide solution was added dropwise to adjust the pH. After stirring for 4 to 12 minutes, the mixture was allowed to stand for 18 to 36 hours, and the ball milling speed was set to 50 to 250 rpm. After ball milling for 20 to 30 minutes, the mixture was sieved through a 100 to 200 mesh sieve to obtain glaze A. (2) milling lithium aluminum silicate powder, cordierite powder and glass fiber at a ball mill speed of 100-200 rpm for 10-20 min, and passing through a 200-300 mesh sieve to obtain a mixed powder; adding the mixed powder to an ethanol solution, stirring for 5-15 min, then sequentially adding a silane coupling agent, a silicate curing agent, a photocuring initiator and a polyvinyl alcohol solution while stirring, dropping a sodium hydroxide solution to adjust the pH, and ultrasonically dispersing the mixture at 40-60 kHz and 150-250 W for 30-50 min to obtain glaze B; (3) mixing glaze A and glaze B to obtain glaze C; (4) Mixing nano zinc oxide, yttrium oxide, chitosan solution and isooctyl acrylate at 60-80° C. for 30-50 min, then adding hexadecyltrimethylammonium bromide and polymethyl methacrylate, and mixing at 70-90° C. for 40-50 min to obtain an antibacterial dopant; (5) adding the antibacterial dopant to glaze C, dispersing it ultrasonically at 40-60 kHz and 150-250 W for 20-40 min, adding polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water, mixing at 50-70 °C for 1-2 h, and curing at room temperature for 12-36 h to obtain an unfired glaze with antibacterial function; The mass ratio of kaolin, diatomaceous earth, talc, calcium carbonate, barium carbonate, magnesium oxide, polystyrene microspheres, polyvinyl pyrrolidone and deionized water in step (1) is 10-12: 8.7-9.5: 4.6-6.2: 3.7-5.1: 4.4-6: 4.1-5.5: 3.5-4.9: 1.1-2.7: 20-26; The mass ratio of lithium aluminum silicate powder, cordierite powder, glass fiber, ethanol solution, silane coupling agent, silicate curing agent, photocuring initiator and polyvinyl alcohol solution in step (2) is 8-10: 5-7: 1.8-3.6: 16-24: 0.8-2.6: 0.86-1.5: 1.49-2.63: 6-12; the polyvinyl alcohol solution is prepared by mixing polyvinyl alcohol and deionized water in a mass ratio of 0.25-0.43:1; The glaze C in step (3) is composed of the glaze A and the glaze B in a mass ratio of 0.71-0.83:0.36-0.48; The mass ratio of nano zinc oxide, yttrium oxide, chitosan solution, isooctyl acrylate, hexadecyltrimethylammonium bromide and polymethyl methacrylate in step (4) is 8.5-10.1:3.6-5.2:2.2-4.6:1.5-2.7:2.1-3.5:0.9-1.8; The mass ratio of glaze C, antibacterial dopant, polyvinyl alcohol solution, silane coupling agent, melamine formaldehyde resin and deionized water in step (5) is 8-12:2.2-3:1.2-2:1.7-3.1:5-10:20-30; the polyvinyl alcohol solution is prepared by mixing polyvinyl alcohol and deionized water in a mass ratio of 0.45-0.51:

1.

2. The process for preparing the unfired glaze with antibacterial function according to claim 1, characterized in that: The concentration of the ethanol solution is 60-80%; the silicate curing agent is sodium silicate adhesive; and the photocuring initiator is dibutyltin dilaurate.

3. The process for preparing the unfired glaze with antibacterial function according to claim 1, characterized in that: The particle size of the nano zinc oxide is 50-90 nm; the concentration of the deacetylated chitosan solution is 0.2-0.5 mol / L.

4. The process for preparing the unfired glaze with antibacterial function according to claim 1, characterized in that: The concentration of the sodium hydroxide solution is 0.4-0.6 mol / L; the pH is adjusted to 7.8-8.6; and the silane coupling agent is at least one of γ-aminopropyltrimethoxysilane and γ-aminopropyltriethoxysilane.

Citation Information

Patent Citations

  • Temperature-sensing ceramic with heat-resistant and cold-proof functions and manufacturing method and application thereof

    CN109836119A